Role of movement in long-term basal ganglia changes: implications for abnormal motor responses - Simola, Nicola; Morelli, Micaela; Frazzitta, Giuseppe; Frau, Lucia (Frontiers in Computational Neuroscience, 2013)
Abnormal involuntary movements (AIMs) and dyskinesias elicited by drugs that stimulate dopamine receptors in the basal ganglia are a major issue in the management of Parkinson’s disease (PD). Preclinical studies in dopamine-denervated animals have contributed to the modeling of these abnormal movements, but the precise neurochemical and functional mechanisms underlying these untoward effects are still elusive. It has recently been suggested that the performance of movement may itself promote the later emergence of drug-induced motor complications, by favoring the generation of aberrant motor memories in the dopamine-denervated basal ganglia. Our recent results from hemiparkinsonian rats subjected to the priming model of dopaminergic stimulation are in agreement with this. These results demonstrate that early performance of movement is crucial for the manifestation of sensitized rotational behavior, indicative of an abnormal motor response, and neurochemical modifications in selected striatal neurons following a dopaminergic challenge. Building on this evidence, this paper discusses the possible role of movement performance in drug-induced motor complications, with a look at the implications for PD management.